GAMBARAN PENGGUNAAN SWAMEDIKASI OBAT SISTEM PENCERNAAN DI APOTEK FORMULA BANJARMASIN - Muliyani Muliyani; Nazhipah Isnani; Nur Aulya Aulya (Jurnal Insan Farmasi Indonesia, 2021)
Self-medicating is the use of medication by a person for self-medication that is done based on the diagnosis of his own symptoms without consulting a doctor or treatment done without a doctor's prescription. Self-medicating tends to increase among the public to overcome symptoms or diseases that are considered mild, South Kalimantan Province has self-medicating with the highest percentage of 85.26% or ranked first in Indonesia in 2020. This study aims to find out the drugs that are often diswamedikasi to treat symptoms or diseases of gastritis, diarrhea, and constipation at Apotek Fomula Banjarmasin. The type of research conducted is descriptive retrospective non-analytical with purposive sampling techniques using secondary data. Based on the results of the study obtained self-medicating gastritis drugs are most commonly used is Promag tablet (31.79%), self-medicating diarrhea drugs that are often used is New Diatab (44%), self-medicating constipation drugs that are often used is Dulcolax tablets (52%).